On the realization of first-order current-mode AP/HP Filter - Tangsrirat, Worapong (My University, 2013)
A compact circuit topology for the realization of the current-mode first-order allpass (AP) and highpass (HP) filters is described. The proposed circuit contains a minimum number of components, i.e., eight bipolar transistors, one grounded capacitor, and one biasing current source. The advantages of this circuit are the use of only grounded capacitor as a passive element, the electronic tunability of its parameters and its potential for lowvoltage operation. Owing to the pole frequency of the filter circuit is normally dependent on temperature; a lowvoltage translinear-based current source circuit for temperature compensation is also suggested. Some simulation results achieved through PSPICE program and experimental test results are also reported, which demonstrate the effectiveness of the proposed circuit.
Keywords: Allpass (AP); Current-mode; First-order filter; Highpass (HP); Integrated circuit